Outcomes of Children Presenting with Button Battery in Esophagus: A Retrospective Review - Gyawali, Bigyan R; Sharma Guragain, Rajendra P; Neupane, Yogesh; Dutta, Heempali; Shrestha, Lava; Pradhananga, Rabindra B (Journal of Institute of Medicine Nepal, 2020)
Introduction Foreign body in esophagus is a common ENT emergency. Button batteries tend to have more grievous outcomes due to caustic mucosal injury to the esophagus. The objective of our study was to review the clinical profile and outcomes of the paediatric population in our center who presented with button battery in esophagus following accidental ingestion.MethodsThis was a retrospective study conducted in Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Hospital records of all the patients who presented with button battery esophagus and underwent rigid oesophagoscopic removal from January 2013 to January 2019 were reviewed and analyzed for patient demographics, time interval between ingestion and presentation, site of impaction, status of oesophageal mucosa at the time of rigid oesophagoscopic removal of the battery, early post-operative complications, outcomes at the time of discharge and on follow-up.ResultsOur final sample size was 11 and all cases were